Extending access to remote labs from mobile devices in educational contexts - Rochadel, Willian (2014)
This paper describes how to extend the access to remote experiments from mobile devices, aiming to better engage digital native students who expect a more interactive and ubiquitous access mode. The extension is based on features of HTML5 and the jQuery Mobile framework, which allow accessing the experiments from different operating systems via the browser or native applications. As a result, users have a richer interaction mode with the experiments, which includes access from simple hand-held devices such as smartphones and PDAs. Extending the access to remote experiments, from simple devices, enables its use in other educational stages, such as high schools, where teachers struggle to engage students in STEM learning. By enabling students to use their everyday "technological companions", e.g. cellular phones, to access remote experiments, we seek to increase the educational value of this technology-enhanced learning resource.